Collective access to justice : assessing the potential of class actions in England and Wales - Molavi, Michael (Bristol : Bristol University Press, 2021)
At a time when the collective redress landscape is undergoing a period of transformative change, this important and timely research focuses on class actions in England and Wales. Aiming to promote access to justice, this pioneering work separates fact from fiction in an easily digestible way, offering progressive solutions for reform.
Title from publisher's bibliographic system (viewed on 04 Jan 2022).
Keywords: Class actions (Civil procedure) -- England; Class actions (Civil procedure) -- Wales